Molecular dynamics modelling of the stress-strain response of β-sheet nanocrystals - Tasseven, Cetin; Akdere, Unsal; Gunay, Seckin D.; Aksakal, Baki (ELSEVIER, 2025)
Molecular dynamics simulations were conducted on two model antiparallel beta-sheet crystallites [GA]n and [GAS] n to study deformation in chain, sheet stacking, and hydrogen bonding directions under uniaxial loading. In chain direction, both models were mechanically stable, even beyond the 570 K amorphousation temperature of silk fiber; however, [GA]n model displayed higher yield strain, stress, elastic modulus, and resilience than [GAS] n. In transverse directions, they had similar stress-strain behavior and demonstrated significant anisotropic mechanical behavior. Hence, inclusion of an amino acid with a rich side chain group extending between beta-sheets reduces the stiffness of crystallite in chain direction. Serine and alanine residues maintained existing H-bonds and established new ones during stretching in chain direction and shrinking in transverse directions which affected the mechanical response near the yield point. Comparison between beta-sheet crystallite and PPTA (Kevlar) showed that the mechanical performance of these crystal polymers were very similar in chain direction, but contrarily beta-sheet crystallite had higher stiffness in H-bonding and sheet stacking directions than PPTA. This study may provide a guideline in designing of polyaminoacid based biocompatible materials with superior mechanical performance.
Keywords: beta-sheet crystals; Molecular dynamics; Stress-strain; Mechanical properties; Hydrogen bonding; BOMBYX-MORI SILK; SPIDER SILK; STRENGTH; TOUGHNESS; NANOSTRUCTURE; TEMPERATURE; MECHANICS; CHAIN; Materials Science